the PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP PERUBAHAN KECEMASAN PASIEN PENYAKIT JANTUNG KORONER - Bela Amaliya; Parellangi Parellangi; Nurul Kartika Sari (MNJ (Mahakam Nursing Journal), 2021)
The prevalence of coronary heart disease has a tendency to raise up every year. Patient has anxiety because of ineffective copping at the onset of the symptoms, insufficient knowledge about the disease and tendency of hearing the death treat. Research is to know the effect of giving the handheld finger relaxation on anxiety changes to the patients with coronary heart disease at ICCU Room, Abdul Wahab Sjahranie Hospital. This Study used Quasi Experiment pre test and post test without control. sampling technique was Non Probability sampling (Non ramdom sample) which was consecutive sampling type. The result of this study shown there was the effect of giving handheld finger relaxation on anxiety changes to the patients with coronary heart disease at ICCU Room, Abdul Wahab Sjahranie Hospital. It is shown with p Value 0,000 (p>0,05) where mean value was 15,00 before intervention shown the level of anxiety was medium, and mean value 10,00 after intervention shown the level of anxiety was low. The handheld finger relaxation can reduce the anxiety of the patients with coronary heart disease. Key words : Handheld finger relaxation, anxiety, coronary heart disease